(528) محاضرات في المنظمات الاقتصادية الدولية Lectures on International Economic Organizations - محمد علي الجارحي (معهد التخطيط القومي, 2026)
تتناول هذه المذكرة الصادرة عن معهد التخطيط القومي عام 1976 تقييماً نقدياً لعمل المنظمات الاقتصادية الدولية القائمة آنذاك في المجالات النقدية والتجارية، مع التركيز على الانقسامات السياسية بين ثلاث مجموعات رئيسية: الكتلة الأنجلوسكسونية بقيادة أمريكا، ومجموعة السوق الأوروبية المشتركة بقيادة فرنسا، ومجموعة دول العالم الثالث. ويحلل البحث كيف أدى تعارض المصالح بين هذه الكتل إلى إضعاف دور صندوق النقد الدولي والاتفاقية العامة للتجارة والجمارك (GATT) في حل الأزمات العالمية، مبيناً أن الدول المتقدمة صممت هذا النظام للحفاظ على هيمنتها، بينما تنظر إليه الدول النامية بعين الشك وتعتبره وسيلة تزيد الأغنياء غنى والفقراء فقراً.كما يسلط الملف الضوء على التحديات النقدية التي واجهت النظام الدولي بعد انهيار نظام الذهب وظهور أزمة "ندرة الدولار"، مستعرضاً دور المصرف الدولي في تمويل التنمية والعقبات التي فرضتها سياساته المحافظة على الدول المتخلفة. ويناقش البحث بعمق مطالب الدول النامية في حماية صناعاتها الناشئة والحصول على قروض ميسرة، مشيراً إلى أن أزمة الطاقة عام 1973 منحت هذه الدول قوة تفاوضية جديدة مكنتها من فرض "حوار" مع العالم المتقدم عبر مؤتمرات التجارة والتنمية (UNCTAD)، بهدف إعادة صياغة النظام الاقتصادي الدولي ليكون أكثر عدالة ونفعاً للمجتمع العالمي. This 1976 memorandum from the National Planning Institute offers a critical assessment of the work of existing international economic organizations in the monetary and trade sectors, focusing on the political divisions among three main groups: The Anglo-Saxon bloc led by the United States, the European Economic Community (EEC) led by France, and the Third World. The research analyzes how the conflicting interests among these blocs weakened the role of the International Monetary Fund (IMF) and the General Agreement on Tariffs and Trade (GATT) in resolving global crises. It argues that developed countries designed this system to maintain their dominance, while developing countries view it with suspicion, considering it a tool that further enriches the rich and impoverishes the poor. The memorandum also highlights the monetary challenges facing the international system after the collapse of the gold standard and the emergence of the dollar shortage, examining the role of the World Bank in financing development and the obstacles its conservative policies imposed on developing countries. The research discusses in depth the demands of developing countries to protect their emerging industries and obtain concessional loans, noting that the 1973 energy crisis gave these countries new negotiating power that enabled them to impose a "dialogue" with the developed world through the Conferences on Trade and Development (UNCTAD), with the aim of reformulating the international economic system to be more just and beneficial to the global community.